Comparison of the effects of autologous and allogeneic purified platelet-rich plasma on cartilage damage in a rabbit model of knee osteoarthritis - Wang, Lingling; Zhao, Luting; Shen, Lianwei; Fang, Qilin; Yang, Zhenglei; Wang, Rongrong; Wu, Qing; Xie, Yulei (Frontiers in Surgery, 2022)
Background: Purified platelet-rich plasma (P-PRP) is gradually being used in the treatment of osteoarthritis (OA), and its sources are mainly divided into autologous and allogeneic blood. However, it is unclear whether autologous PRP is more effective or allogeneic PRP is superior. Objective: In this study, autologous and allogeneic P-PRP was injected at early stage of KOA in rabbits, and then the differences in the efficacy of the two P-PRPs against KOA were compared from several perspectives, including pathological histology and immunohistochemistry. Method: Experimental rabbits were divided into normal group (n=8), model group (n=8), autologous P-PRP group (n=8), and allogeneic P-PRP group (n=8) using a random number table method. The normal and model groups did not receive any treatment, and the autologous P-PRP and allogeneic P-PRP groups received intra-articular injections of autologous and allogeneic P-PRP, respectively. changes in the gross specimens of the knee joints of the experimental rabbits in each group were observed, and the histopathological changes of chondrocytes were observed by HE-stained sections of articular cartilage, and the expression of chondrocytes Bone morphogenetic protein-2 (BMP-2) and Sox9 were detected by immunohistochemistry. Resluts: Compared with the allogeneic P-PRP group, the differences were statistically significant (P<0.05) in the gross specimens and pathological histological findings in the autologous PRP group. Immunohistochemical results showed that the expression of BMP-2 and Sox9 was elevated in both the autologous P-PRP group and the allogeneic P-PRP group compared with the model group, and the expression of BMP-2 was higher in the autologous P-PRP group than in the allogeneic P-PRP group, with a statistically significant difference (P<0.05), while there was no difference in the expression of Sox9 between the two groups (P>0.05). Conclusion: Intra-articular injection of autologous P-PRP activated the expression of BMP-2 and Sox9 in chondrocytes and effectively improved KOA cartilage repair and reduced bone redundancy and joint fluid formation, and its efficacy was superior to that of intra-articular injection of allogeneic P-PRP.